Synthetic and Natural Plant Growth Regulators for Growing Seedlings of Tree Species - Nadezhda P. Chernobrovkina; Anastasiya V. Egorova; Elena V. Robonen; Karina G. Nelaeva (Лесной журнал)
Technologies for growing planting stock with a closed root system, including a multi-rotation mode, are being actively introduced and improved. In the forest nurseries of the middle taiga subzone of the Russian Federation, its use is difficult due to the short growing season and, as a consequence, the insufficient adaptation of the 2nd rotation seedlings to the conditions of the winter season and their failure to reach standard sizes. One of the effective methods for improving plant growth and their adaptability to adverse environmental conditions is the use of growth stimulants. Numerous studies have been conducted to identify the effect of such preparations on seed germination and the development of tree seedlings in order to optimize the growing regime. The aim of this article is to summarize and systematize the results of studies on the use of plant growth regulators in the cultivation of seedlings in forest nurseries. A classification of plant growth regulators has been given: synthetic ones based on various sources and biostimulants based on natural raw materials – acidic, microbiological and plant extracts. The latter include extracts of woody and herbaceous plants and marine algae. The composition of biologically active compounds in preparations from coniferous and deciduous foliage has been considered. The article presents information on the peculiarities and effectiveness of synthetic growth regulators and biostimulants on the development of seedlings and their survival rate when planted in a forest cultivation area. The characteristic features of the process of obtaining preparations from foliage have been presented, close attention has been paid to the presence of phytohormones in these preparations, depending on the time of selection of planting stock in daily dynamics. The use of synthetic growth regulators, as well as biostimulants, is a reliable way to improve seed germination and the growth of tree seedlings when grown in forest nurseries. The choice of growth regulators for specific purposes when preparing planting stock is based on experimental studies taking into account the plant species, economic feasibility, ecology, climate and raw material resources of the region.